Dawn of desegregation J.A. De Laine and Briggs v. Elliott - Gona, Ophelia De Laine (University of South Carolina Press, 2011)
"Though De Laine and the brave parents who filed Briggs v. Elliott initially lost their lawsuit in district court, the case grew in significance when the plaintiffs appealed the decision to the U.S. Supreme Court. Three years after the appeal, the Briggs case was one of the five lawsuits that shared the historic Brown decision. However, the ruling did not prevent De Laine and his family from suffering vicious reprisals from vindictive white citizens. In 1955, after he was shot at and his church was burned to the ground, De Laine prudently fled South Carolina in order to save his life. He died in exile in Charlotte, North Carolina, in 1974. Fifty years after the Supreme Court's decision, De Laine was awarded the Congressional Gold Medal in recognition of his role in reshaping the American civil rights landscape."--Book jacket.